Analisis Kemampuan Pemecahan Masalah Matematis Siswa SMA Kelas XI Pada Materi Lingkaran - Elly Putri Sholihah; Sugiyanti Sugiyanti; Rasiman Rasiman3; Dwi Astuti (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2024)
This research aims to describe the stages of student problem solving based on the Polya stages in circle material. Based on these objectives, this research is included in descriptive qualitative research. Data collection was carried out on class XI students at SMA Negeri 2 Semarang selected using purposive sampling. The subjects chosen in this research were 6 students, consisting of two students with low initial abilities, two students with medium initial abilities, and two students with high initial abilities. The data used was verified using source triangulation. The results of this research show: 1) S-5 and S-6 subjects with low initial abilities were able to understand the problem, were less able to prepare a resolution plan, were less able to carry out the resolution plan, and were less able to re-examine. 2) S3 and S-4 subjects with moderate initial abilities were able to understand the problem even though S-3 subjects had not written down what was asked in the problem, were able to prepare a solution plan, were less able to carry out the solution plan, and were less able to recheck. 3) S-1 and S-2 subjects with high initial abilities are able to understand the problem, less able to prepare a resolution plan, less able to carry out the resolution plan, and less able to re-examine.